Jinnah, Pakistan, and Islamic Identity: By Akbar S. Ahmed Routledge, New York; 1997, 274 pp. + xxix. (American Journal of Islam and Society, 1998)
Dr. Akbar S. Ahmed is probably the most published author in Pakistan. His published works, some of which have earned excellent reviews, make a fonnidable list. Asperhaps the best known contemporary Muslim anthropologist, his commitment to the discipline,despite his avocation of being an administrator, is the key to his success. Whatsets Ahmed apart from most Pakistani authors is that his writings are informed by theoreticalconsiderations and anchored in empirical data. He exudes easy familiarity withmethodology, is creative and imaginative in his approach, and can conceptualize.Moreover, he can intellectu.alize problems and issues. As with his earlier writings, his presentwork is marked by these characteristics.The work is structured around one major theme (Jinnah), and the subthemes of thenature of nationhood, Islam, ethnic and religious identity, the problems of minorities, andthe pervasive and ubiquitous influence of media, race, empire, and other factors. Usingthe methodologies of cultural anthropology, semiotics, and media studies, Ahrnedexplores old ground with new insights and interpretations. What we have here is neitherbiography nor history per se; it is part biography, part history of partition, an explorationof Muslim nationhood and Pakistani statehood, and part the Muslim search for identity, aquest that not only inspired the Muslim struggle for Pakistan during the 1940% but whichis still relevant (e.g., northern Cyprus, Bosnia, Chechnia, Kashmir, Kosovo, Mindanao[the Philippines], Pattani [Thailand], and even for the Turkish minority in Bulgaria).All said and done, it was the critical problem of identity to which Jinnah addressedhimself in the Indian context of the 1930s and 1940s. Thus he represents not onlyPakistan, but also a manifestation of the very search for identity in the present largerMuslim world context. His solution to the problems of marginalization, alienation, andeven exclusion of Muslims from the corridors of power serves as a beacon to Muslimcommunities struggling for identity, self-expression, and self-realization. Hence the relevanceof Jinnah to the modem Muslim world ...